Environmental Science : - Wright, Richard T. (Benjamin Cummings, 2011)
By emphasizing the memorable themes of science, sustainability and stewardship, the Eleventh Edition of this popular textbook helps you understand the science behind environmental issues and what you can do to build a more sustainable future. This thorough revision features updated content, graphics, and photos, plus the addition of new co-author Dorothy Boorse.